Diapause hormone directly stimulates the prothoracic glands of diapause larvae under juvenile hormone regulation in the bamboo borer, Omphisa fuscidentalis Hampson - Suphawan Suang (2019)
© 2019 Wiley Periodicals, Inc. Larval diapause in many lepidopteran insects is induced and maintained by high juvenile hormone (JH). In the case of the bamboo borer, Omphisa fuscidentalis, the effect of JH is the opposite: The application of juvenile hormone analog (JHA: S-methoprene) terminates larval diapause, unlike in other insect species. Here, we analyzed the expression of JH-receptor Met, DH-PBAN, and Kr-h1 in the subesophageal ganglion (SG) from October to April using semi-quantitative polymerase chain reaction (PCR). The results show that OfMet and OfDH-PBAN messenger RNA in the SG are mainly expressed during the larval diapause stage, while OfKr-h1 increases during the pupal stage. Using tissue culture techniques and an enzyme-linked immunosorbent assay (ELISA), diapause hormone (DH) was found to induce ecdysteroidogenesis in the culture medium of the prothoracic gland (PG) after incubation for 30 min with 25 ng and 50 ng of DH. Thus, DH is a novel stimulator for the PG. We identified a DHR homolog in the bamboo borer and confirmed that it is expressed in the PG. In addition, for in vitro experiments, DH increased the expression levels of OfDHR, OfEcR-A, and ecdysone-inducible genes in the PG. These results demonstrate that DH can function as a prothoracicotropic factor, and this function of DH might be through of DHR expressed on PG cells. Consequently, DH is one of the key factors in larval diapause break which is triggered by JH in the bamboo borer, O. fuscidentalis.